On the determination of the anisotropic plasticity of metal materials by using instrumented indentation. (5th December 2016) - Wang, Mingzhi; Wu, Jianjun; Zhan, Xuepeng; Guo, Ruichao; Hui, Yu; Fan, He
Abstract: In this paper, an inverse computation approach is proposed to estimate the anisotropic plastic properties of materials by using the instrumented indentation. For the anisotropic materials considered in the present study, the plastic properties (e.g. the stress strain curves) along orthogonal directions (e.g. longitudinal vs. transverse) are different. This approach is based on weighting the information collected from instrumented indentation and the conventional optimization algorithm. The ill-posed nature of using only the indentation load-displacement curve in the inverse analysis process is investigated. To obtain a unique solution, the pile-up values around indenter are considered as important additional information. Results show that, by introducing the pile-up values, the inverse analysis gives well-posed solution of the anisotropic plastic properties. The new approach is applied on two metal materials, and the anisotropic properties obtained from indentation and uniaxial tests show good agreement. Graphical abstract: Highlights: A new method is proposed to estimate the anisotropic plasticity of metal materials by using instrumented indentation. The ill-posed nature of using only the indentation P-h curve in the inverse analysis process is investigated. By introducing the pile-up effects, the well-posed solution is obtained. Effectiveness of the new approach is verified by application on two engineering materials.